Line tracking robot using vision systems - Che Rohazli, Che Mazlam (2010)
This project was about to build a robot that can detect straight white line using vision system (MATLAB). The aim of this paper was to prove that vision system can be used to detect line. The software that used was MATLAB R2010a. The project was divided into four phases. Phase 1: Hardware Design, Phase 2: Software Implementation and Phase 3: Hardware Interfacing. The main part for this project was about the software implementation. So, the paper will focus on the using of the MATLAB software. The main parts that used in the MATLAB software were Image Acquisition Toolbox and Image Processing Toolbox. The techniques that had been apply in the project were Image Enhancement Technique, Image Filtering Technique and Image Restoration Technique. The project had make realtime database using webcam. The function of the webcam was detecting line and then transmits the image data into the PC. After that, as the interfaced devices, PCI 1710 (Data Acquisition Card) was used to make connection between PC and the robot